Perception and Practice of Nepalese Adult and Adolescent Patients towards Orthodontic Treatment (Orthodontic Journal of Nepal, 2015)
Introduction: Patient’s perception and practice on ongoing treatment is very important to evaluate the practice management.Objective: To assess the perception and practice of Nepalese orthodontic patients towards orthodontic treatment and to find the difference between adolescent and adult.Materials & Method: A structured questionnaire with 3-point Likert scale was used among 536 orthodontic patients at eight orthodontic centers. The data were rescored based on their views and depicted on good, moderate and poor levels. The difference in perception and practice between adolescent and adult patients was analyzed using Mann-Whitney U test.Result: More than 80% patients feel that, orthodontist’s dealing and skill is good, while more than two-third feel that orthodontic treatment is expensive. More than half adolescent and two-third adult patients restrict certain food due to braces; about one third adolescent and one-fourth adult patients are careless on appliance breakage. More number of adult patients consume analgesics compared to adolescents. There was significant difference in perception about ‘duration of treatment’ and ‘chance of relapse’, and practice on ‘food restriction’ and ‘carelessness of appliance’ between adolescent and adult patients.Conclusion: Nepalese orthodontic patients possess good perception about orthodontist’s dealing and skill, and good practice on regular brushing habits. Adolescent patients lack positive perception about duration of treatment and majority of patients feel that orthodontic treatment is expensive. Adult patients have better perception and practice about the orthodontic treatment than adolescent in all parameters studied except for ‘cost of treatment’ and ‘use of analgesics’.